Evaluating Functional Outcomes in Reanimation Surgery for Chronic Facial Paralysis: A Systematic Review. Issue 3 (March 2021) - Rodriguez Colon, Ricardo; Park, Jenn J.; Boczar, Daniel; Diep, Gustave K.; Berman, Zoe P.; Trilles, Jorge; Chaya, Bachar F.; Rodriguez, Eduardo D.
Abstract : Background: Chronic facial paralysis can lead to significant functional and psychosocial impairment. Treatment often involves free muscle flap-based facial reanimation surgery. Although surgical techniques have advanced considerably over the years, consensus has yet to be reached for postoperative outcome evaluation. To facilitate outcome comparison between the various techniques for free muscle-flap-based reanimation, a standardized, widely accepted functional outcomes assessment tool must be adopted. Methods: In accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, we performed a systematic review of the PubMed, Cochrane, and Embase databases to identify the reported functional outcome measurement tools used in the free muscle flap-based reanimation literature. Results: The search yielded 219 articles, 43 of which met our inclusion and exclusion criteria. We noted an increase in publications reporting the utilization of objective measures over time, particularly software-based tools, as well as increased utilization of patient reported outcomes measures. Conclusions: Based on the trends identified in the literature, we suggest standardization of outcome measures following facial reanimation surgery with free muscle-flap using a combination of the Facial Assessment by Computer Evaluation (FACEgram) software and the Facial Clinimetric Evaluation (FaCE) Scale.